Respiratory Training and Plasticity After Cervical Spinal Cord Injury - Randelman, Margo; Zholudeva, Lyandysha V.; Vinit, Stéphane; Lane, Michael A. (Frontiers in Cellular Neuroscience, 2021)
While spinal cord injuries (SCIs) result in a vast array of functional deficits, many of which are life threatening, the majority of SCIs are anatomically incomplete. Spared neural pathways contribute to functional and anatomical neuroplasticity that can occur spontaneously, or can be harnessed using rehabilitative, electrophysiological, or pharmacological strategies. With a focus on respiratory networks that are affected by cervical level SCI, the present review summarizes how non-invasive respiratory treatments can be used to harness this neuroplastic potential and enhance long-term recovery. Specific attention is given to “respiratory training” strategies currently used clinically (e.g., resistance training) and those being developed through pre-clinical and early clinical testing (e.g., intermittent chemical stimulation via altering inhaled oxygen (hypoxia) or carbon dioxide stimulation). Consideration is also given to the effect of training on non-respiratory (e.g., locomotor) networks. This review highlights advances in this area of pre-clinical and translational research, with insight into future directions for enhancing plasticity and improving functional outcomes after SCI.